2022
DOI: 10.3390/jcs6120381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alumina and Silicon Carbide Nanoparticle-Infused Polymer Matrix on Mechanical Properties of Unidirectional Carbon Fiber-Reinforced Polymer

Abstract: Unidirectional carbon fiber-reinforced polymer nanocomposites were developed by adding alumina (Al2O3) and silicon carbide (SiC) nanoparticles using ultrasonication and magnetic stirring. The uniform nanoparticle dispersions were examined with a field-emission scanning electron microscope. The nano-phase matrix was then utilized to fabricate the hybrid carbon fiber-reinforced polymer nanocomposites by hand lay-up and compression molding. The weight fractions selected for Al2O3 and SiC nanoparticles were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…In the present work, superior mechanical properties have also been obtained for the epoxy carbon fiber based on a graphene addition of 0.8 wt%. Thus the information on the research findings 33,34 and the present work are in agreement with each other.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present work, superior mechanical properties have also been obtained for the epoxy carbon fiber based on a graphene addition of 0.8 wt%. Thus the information on the research findings 33,34 and the present work are in agreement with each other.…”
Section: Resultssupporting
confidence: 92%
“…The nano hybridization effect of increased nano concentration in both NGP and nanographene and silica hybrid additions showed the highest tensile strength and flexural strength for the highest concentrations. Further, Shahabaz et al 34 have reported the effect of nanofillers viz Al 2 O 3 and SiC in the CFRP hybrid composites with the primary objective of studying the hardness and tensile properties. Compared to unfilled composites, the nanofillers added comparably have indicated better tensile properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The most commonly used nanoparticles in polymer nanocomposites are Al 2 O 3 , h-BN, SiC, SWCNT, and MWCNT. [5,6] Ruan et al have used urea melt to aminate GO to produce NH 2 -GO. Furthermore, the prepared NH 2 -GO was converted into NH 2 -rGO through a thermal reduction method.…”
Section: Enhancement Of Thermal Conductivity Of Polymers Using Nanopa...mentioning
confidence: 99%
“…[ 4 ] The most commonly used nanoparticles in polymer nanocomposites are Al 2 O 3 , h‐BN, SiC, SWCNT, and MWCNT. [ 5,6 ]…”
Section: Introductionmentioning
confidence: 99%